ROLE OF DOPPLER ULTRASOUND IN IUGR TO IMPROVE FETAL OUTCOMES (The Research of Medical Science Review, 2025)
Objective: The aim of this study was to identify the role of doppler ultrasonography for the detection of IUGR, to explore its impact on different fetal outcomes. The study further attempted to determine the relationship between the doppler waveform patterns of IUGR, the likelihood of a C-section, and low birth weight.Study Design: prospective cross-sectional studyStudy Setting: Obstetrics and Gynecology Department, JPMC, Karachi.Study Duration: Six months (from June to Nov, 2024)Methodology: 100 participants with high-risk, clinically suspected IUGR, 31–41 weeks pregnancies participated in prospective research. The patients were monitored up to delivery, and the greyscale and doppler results were compared to the infants' birth weights.Results: The HC/AC ratio was determined to have the best sensitivity (70.2%), oligohydramnios to have the highest specificity (98%), and C/U ratio was found to be highly specific (98.8 %). The C/U ratio's sensitivity was discovered as 67.4%. The least sensitive was the middle cerebral artery (26.7%). The relationship between an aberrant uterine artery PI and a cesarean delivery result was found to be quite significant (p-value = 0.0095), however no statistically significant correlation between an aberrant umbilical artery, fetal middle cerebral artery, and C/U ratio PI values with cesarean section was found.Conclusion: In order to identify IUGR, oligohydramnios and HC/AC ratio are both very specific parameters. The best measure for IUGR diagnosis in the third trimester is the C/U ratio, which was found to be better as compared to oligohydramnios and HC/AC ratio in both sensitivity and specificivity.